SANGSI PELAKU PERNIKAHAN ILEGAL - Moh. Asy'ari Muthhar; Imam Musyafirudin (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2022)
This article is the result of library research. This research is included in the category of normative legal research. This research discussion aims to explain the istiḥān argument against the draft criminal sanctions law for perpetrators of illegal marriages. The researcher analyzed the data using istihsān bi al-maqāsid sharī'ah theory. The findings of this study are that the draft law regarding the provision of criminal sanctions against perpetrators of illegal marriages is not effectively implemented. This argument is based on the reading of legal material data with the theory of Istiḥsān bi maṣlaḥat al-mursalah. The legal reasoning put forward by Toeri istihsan is first, there are still many inadequate facilities in serving the implementation of Law Number 1 of 1974; second, less than optimal bureaucracy and background problems or motivation in carrying out marriages outside the institution of marriage registrar officials as well as conflicting government regulations with one another. The research data is read with the istiḥsān theory and results in the absence of mashlahah if the rules of criminal sanctions are applied. Keywords: Perpetrators of illegal marriages, Draft law, istiḥsān Daftar Pustaka Al Amin, Habibi. "Penciptaan Adam; Mendialogkan TafsiR Marah Labid dengan Teori Keadilan Gender." An-Nuha: Jurnal Kajian Islam, Pendidikan, Budaya Dan Sosial 1.1 (2014): 17-44. Al Amin, Habibi. "Tafsir Sufi Lataâ€™ if al-Isyarat." SUHUF 9.1 (2016): 59-77. Al Amin, Habibi. "Guardians Concept in Qur'an Perspective." Shakhsiyah Burhaniyah: Jurnal Penelitian Hukum Islam 6.1 (2021): 95-114. Abd. al-Rahman al-Jazairi, 1969. al-Fiqh ‘ala al-Madzahib al-’Arba’ah, Kairo: Maktabah al- Tijariyyah. Abd. Rahman Dahlan, 2011. Ushul Fiqh, Cet. Ke-3, Jakarta: Amzah. Abdul Wahab Khallaf, Ilmu Ushulul Fiqh, Terj. Noer Iskandar Al-Bansany, dkk, 1989. “Kaidah-Kaidah Hukum Islam”, Jakarta: CV Rajawali. Abdurrahman Al-Jaziri, 1986. Kitab ‘ala Mazahib al-Arba’ah. (Beirut Libanon: Dar Ihya al-Turas al-Arabi. Abdurrahman, 2001. Kompilasi Hukum Islam, Jakarta : Akademika Pressindo. Abu Thayyib Muhammad Syamsul Haq, t.th. Awn al-Ma’bud ‘An Syarh Sunan Abu Dawud, Juz II, Beirut : Dar al-Im al-Malayin. Adillah, Siti Ummu. 2011. Analisis Hukum Terhadap Faktor-faktor yang melatarbelakangi Terjadinya Nikah Siri dan Dampaknya terhadap Perempuan (istri) dan Anak-anak. Jurnal Dinamika Hukum, Vol. 11. Al-Ainaini, Badran Abu. T.th. Ushul Fiqh al-Islamiy. Mesir: Mu‟assasah Syabab alIskandariyah. Alam, Syariful. 2011. Kontroversi Rancangan Undang Undang Hukum Materiil Peradilan Agama (RUU HMPA) (Studi Pandangan Para Kiai Ponorogo tentang Sanksi Pidana Perkawinan yang tidak dicatatkan), Tesis (Malang: Universitas Islam Negeri Maulana Malik Ibrahim. Al-Amidi, Abu al-Hasan ‘Ali bin Abi ‘Ali (t.t.), al-Ihkam fi Us ul al-Ahkam, j. 4. Beirut: Dar al-Kutub al-‘Ilmiyyah. Al-Amidy, Abu al-Hasan Ali. 1983. Al-Ihkam fi ushul al-ahkam. Beirut: Dar al-Kutub al-Ilmiyah. Al-Asyqor, Usamah. T.th. Mustajaddat Fiqhiyyah fi Qodhoya Zawaj wa Tholaq. Al-Bazdawi, ALauddi Abdul Aziz. 1991. Kasyfu al-Asrar Syarhu Ushul al-bazdawi, Tahqiq Muhammad al-Mu’tshim Billahi. Beirut: Dar al-kitab al-‘Arabi. Al-Bukhari, ‘Ala’ al-Din ‘Abd al-‘Aziz bin Ahmad bin Muhammad, (1997), Kasyf al-Asrar ‘an Us ul Fakhr al-Islam al- Bazdaw I , j. 4. Beirut: Dar al-Kutub al-‘Ilmiyyah. Al-Dimsyaqy, Ibnu Qudamah. 1978. Raudhah an-nadhir wa junnah al-anadhir. Beirut: Muassasah al-Risalah. Al-Ghazali, Abu Hamid Muhammad bin Muhammad (1997), al-Musta sfa min ‘Ilm al-Us ul, j. 1. Beirut: Mu’assah al-Risalah. Ali Ahmad al-Jurjani, 1974. Hikmah al-Tasyre’ wa Falsafatuhu, Beirut, Dar al-Fikri. Al-Jazari, Syamsuddin Muhammad Ibn Yusuf. 1993. Mi‟râj Al-Minhâj Syarh Minhâj Al-Wushûl Ila Ilmi Al-Ushûl Li Al- Qâdhî Al-Baidhâwî, cet I. jilid II. Al-Mahalli, Jalal al-Din Muhammad bin Ahmad (1999), Jam‘ al-Jawami‘, j. 2. Beirut: Dar al-Kutub al-‘Ilmiyyah. Al-Qadi al-‘Idid, ‘Abd al-Rahman bin Ahmad al-Iiji (2000), “Syarh al-‘I did ‘ala Mukhtasar al-Muntaha al-Us uli”. Beirut:Dar al-Kutub al-‘Ilmiyyah. Al-Qathan, Manna’. 1996. Tarikh Tasyri‟ Al-Islami (At-Tasyri‟ Wa Al-Fiqh), Muassasah Risalah. Al-Tufi, Sulayman bin ‘Abd al-Qawi bin al-Karim. (1987). Syarh Mukhtasar al-Rawdah. j. 3. Kaherah: Muassasah al-Risalah. Al-Zarkasyi, Badr al-Din Muhammad bin ‘Abdullah, (2000), al-Bahr al-Muhit fi Us ul al-Fiqh, j. 4. Beirut: Dar al-Kutub al-‘Ilmiyyah. Amnawaty dan Wati Rahmi Ria, 2008. Hukum dan Hukum Islam. Bandar Lampung: Penerbit Universitas Lampung. Andi Hamzah, 1983. Suatu Tinjauan Ringkas Sistem Pemidanaan di Indonesia, Jakarta: Akademika Pressindo. Aziz, Amir Abdul. 1997. Ushûl Fiqh Al-Islâmî, t.tp: Darussalam. Fakhr al-Din al-Razi, Muhammad bin ‘Umar bin al-Husayn, (1992), al-Mahs ul fi Us ul al-Fiqh, j. 6. Beirut: Mu’assah al-Risalah. Fakhr al-Din al-Raziy,t.th. Mafatih al-Ghayb (Tafsir al-Kabir), Juz III, Beirut : Mu’assah al-Risalah. Ibn al-Hajib, Jamal al-Din ‘Uthman bin ‘Umar (2000), “Mukhtasar al-Muntaha al-Us uli”, Beirut: Dar al-Kutub al-‘Ilmiyyah. Ibn al-Najjar, Taqi al-Din Muhammad bin Ahmad (1997), Syarh al-Kawkab al-Munir, j. 4. Riyadh: Maktabah al-‘Abaykan. Ibn al-Qayyim al-Jauziyyah, t.th. I’lam al-Muwaqqi’in, Jilid VI, Beirut : Dar al-Fikr. Ibn Qudamah, ‘Abdullah bin Ahmad. (1987). Rawdah al-Na zir. j. 3. Kaherah: Mu’assasah al-Risalah. Ibnu Nujaim, t.th. al-Asybah wa Nadhair, Beirut : Dar al-Fikr. Taufiqurrahman, Zaky Fajar, and Habibi Al Amin. "Desain Pembelajaran Literasi Kitab Kuning Melalui Metode Sorogan dalam Meningkatkan Pemahaman Agama Islam." Syntax Literate; Jurnal Ilmiah Indonesia 6.2 (2021): 1467-1474.